Reprioritizing life: a conceptual model of how women with type 1 diabetes deal with main concerns in early motherhood. Issue 1 (1st January 2017) - Carlsson, Ing-Marie; Berg, Marie; Adolfsson, Annsofie; Sparud-Lundin, Carina
ABSTRACT: Purpose: Becoming a mother is related to increased demands for women with type 1 diabetes mellitus, and more research is needed to identify their needs for support in everyday living. Thus, the aim of this study was to explore the main concerns in daily life in early motherhood for women with type 1 diabetes and how they deal with these concerns. Method: A grounded theory study was conducted in which 14 women with type 1 diabetes were interviewed individually 7 to 17 months after childbirth. Results: A conceptual model was identified with the core category "reprioritizing life", and three related categories: adjusting to motherhood, taking command of the diabetes, and seeking like-minded women. Becoming a mother was a turning point towards a greater awareness and acceptance of prioritizing diabetes management and health, and thus, life. There was a gap in provision of diabetes care after birth and during the time of early motherhood compared with during pregnancy. Conclusions: Healthcare contacts already planned before delivery can promote person-centred care during the whole period from pregnancy to motherhood. Moreover, providing alternative sources for health information and peer support could improve the life situation during early motherhood.